Analyses of the semantic features of the lexical bundle [(VERB) PREPOSITION the NOUN of] - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
Author/s Siaw-Fong Chung F.Y. August Chao Tien-Yu Lan Yen-Yu Lin National Chengchi University, Taiwan   ABSTRACT This paper investigates twenty-two prepositions in two different lexical bundles - [PREPOSITION the NOUN of] (at the point of, from the perspective of, etc.) and [VERB PREPOSITION the NOUN of] (shouted above the noise of, suffering from the effects of, etc.), the only difference being that the former does not include the head verb that is present in the latter. Strings of constructions were extracted from the British National Corpus and the types of possible verbs, prepositions, and nouns in each possible combination were analyzed. The paper also details an experiment in which the types of nouns under each of the twenty-two prepositions were coded by human subjects in terms of their semantic features. Finally, a computer program was also utilized to calculate the shared meaning of the different VERBs and NOUNs. The results showed that the nouns in [(VERB) PREPOSITION the NOUN of], though they might form clusters of meanings, may not behave in the same way with and without the presence of the verbs.